Net Zero, Net Profit: An Analysis of Offshore UK Carbon Capture and Storage - Perry,Alexander Verne Magnus (2023)
The UK government is legally bound to reach net zero greenhouse gas emissions by 2050 as part of its actions to address climate change. One prominent method of decarbonisation is carbon capture and storage (CCS), slated for deployment in two industrial clusters by the mid-2020s. Fossil fuel companies are the operator behind the rollout of this technology: given the historical reticence of these companies to acknowledge or address climate change, this phenomenon bears investigation. Adopting a Marxist framework, this thesis explores the practical involvement of these fossil entities in the proposed deployment of CCS and teases out three underlying mechanisms that explain their involvement. First, CCS can serve a defensive function, extending the operational lifespan of existing capital through incorporating it into storage operations, and justifying the continued use of fossil fuels. Second, conceived of as materialised ideology, CCS can re-legitimise the existence of the fossil bloc in the face of existential threats (climate change and the commitment to reaching net zero) through the ostensible resolution of the climate/capital contradiction. Third, CCS incorporates decarbonisation into the logics of capitalism by opening up a novel realm of accumulation for fossil entities in the form of blue hydrogen. These mechanisms can be viewed as protecting the interests of fossil fuel companies and safeguarding the continued operations of business-as-usual. In making explicit these mechanisms, this thesis can ground future engagement with CCS as an emergent phenomenon and provide space for conceptualising its deployment in different social relations.
Keywords: Marx; primitive fossil capital; carbon capture and storage; CCS; socio-ecological fix; defensive fix; hegemony; green capitalism; materialised ideology